PENGARUH PROGRAM INOVASI JOJOBA (JUMAT OLAHRAGA, JUMAT OLAHRASA, JUMAT BAHAGIA) TERHADAP PEMBENTUKAN KARAKTER PESERTA DIDIK - Kusumawati, Anik; Fajrie, Nur; Fathurohman, Irfai (Journal Prakarsa Paedagogia, 2024)
This research aims to measure the influence of school innovation on the formation of studentâ€™s character in increasing their belief in Almighty God, maintaining a healthy body by exercising, and caring for the environment. This is in accordance with the aim of the National Education System, namely to form the character of a generation that is dignified, has faith and trust in God, has good manners, is able to think creatively, has an independent spirit and has a sense of responsibility. JOJOBA school innovation is an innovation used at SMPN 1 batangan to strengthen the character of students. The research metod use qualitative descriptive approach with data collection techniques through observation, interviews, and documentation studies. The result show that the studentâ€™s haracter is better than before, which has an impact on good school report cards.Â